From a great idea to radical innovation : managing the fuzzy front end of product development projects - Erla Björk Baldursdóttir 1985- (2021)
This paper explores how innovative companies in Iceland, create innovation ideas and foster them through the ‘fuzzy front end’ of the product development process. This is an important phase for all innovation projects, as the uncertainty of the idea and its deliverables needs to be refined before it is turned into a realizable product development project. Most innovation projects can be considered incremental, but radical innovation projects have the potential to radically alter the market or create new ones. The literature favours radical innovation while companies often focus on incremental. Product development projects do not lend themselves well to the linearity of traditional project management as they contain high level of uncertainty and therefore need skilled project managers as well as organisational capabilities to adapt to them and give them space to test, make changes to the scope and trial-and-error their way into radical innovations.